The NITAG Resource Centre (NRC): One-stop shop towards a collaborative platform. Issue 36 (26th August 2015) - Adjagba, Alex; Henaff, Louise; Duclos, Philippe
Abstract It has long been acknowledged that there is little interaction between National Immunization Technical Advisory Groups (NITAGs) in the North and even less between those in the North and those in the South. Three international meetings of NITAGs recommended establishing an international network of NITAGs centred on a core functional structure and platform to facilitate future exchanges. The SIVAC Initiative (as part of a WHO Collaborating Center) followed-up with this recommendation, and launched an interactive platform involving all NITAGs worldwide in an active network and open collaboration: the NITAG Resource Center (NRC), accessible at http://www.nitag-resource.org. The NRC offers NITAG members and secretariats a centralized access to NITAG recommendations from around the world, systematic reviews, scientific publications, technical reports, updates from partners, and upcoming immunization events. A dedicated network manager will proactively update all contents through a strong network of regional and national focal points. The NRC is a first step towards a more fruitful and global collaboration between NITAGs.